A REVIEW ON RAWLS THEORY OF JUSTICE - Said, M.Yasir; Nurhayati, Yati (Scholar Center, 2021)
Justice is an abstract idea and understanding the core concept of various types of justice will help scholars, lawyers and law enforcement to develop and use the theory for legislative drafting, judicial review, case review, in court defense, and legal research and writing. In this paper we discussed the essence of Rawls Justice, the implication and compared it to other theories of justice. Therefore this paper will focused on examining and reviewing John Rawls idea of Justice and how to implement it in society. The method used in this study is doctrinal legal research. The result of this study while we discussed that the three Rawls principles cannot be realized together because one principle collides with another. Rawls prioritizes that the principle of the equal liberty which is lexically maximized precedes the second and third principles. However we believe Justice as Fairness in action should not mean that there is equality but rather emphasizes the concept of balance for the law in providing justice.